Analisis Biomekanika terhadap Efisiensi Gerakan dan Risiko Cedera pada Atlet Bulutangkis: Narrative Literature Review - Azmal Rusmana, Gifar; Gumilar, Agus; Darajat Kusumah Negara, Jajat; Nuryadi (Jayabama: Jurnal Peminat Olahraga, 2025)
Badminton is a sport that demands high movement efficiency and has a significant risk of injury. This study aims to analyze the relationship between biomechanics, movement efficiency, and injury risk in badminton athletes through a narrative literature review. The results of the analysis show that a biomechanics approach can improve understanding of techniques such as smash, lunge, and take-off, thus supporting optimal performance. The integration between biomechanics and motor learning contributes to the formation of correct techniques, especially in young athletes. In addition, biomechanical analysis provides insight into common injury mechanisms, such as shoulder and ligament injuries, and prevention strategies. This study confirms the importance of utilizing biomechanics in the training and coaching of badminton athletes to improve movement efficiency, minimize injury risk, and support the sustainability of athletes' careers.